X70 STEEL CRITICAL CTOD VALUE ANSYS CALCULATION - YE YunQin; MIAO ZhangMu; ZHANG BuAi (Jixie qiangdu)
With the development of ocean engineering,increase in the number of project exploration of Marine oil and gas,natural gas and oil transportation engineering are increasingly developed. UOE production technology of high strength of X70 steel is widely used in oil and gas transportation project,and then the higher the strength of steel,the fracture toughness is lower. We need to determine the identity of the fracture toughness values. Material fracture toughness size can use critical crack tip opening displacement CTOD（ crack tipopening below） to measure. Critical CTOD is important parameters in elastic-plastic fracture mechanics,the size directly reflects the material’s ability to resist cracking. The bigger the critical value of CTOD show that the cracking resistance of materials,the better. Determining the critical value of CTOD is of great significance. On the basis of BS7448 specification of X70 steel critical fracture toughness CTOD was tested,and then by using ANSYS software of X70 steel in terms of CTOD define critical CTOD was calculated,and implement the test and simulation comparison and analysis,safety asses